2017
DOI: 10.3390/ijerph14050480
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Methods for Decontamination of Microcystin in Water Using Cold Plasma and UV with Reusable TiO2 Nanoparticle Coating

Abstract: Microcystins (MCs) are a family of cyanotoxins and pose detrimental effects on human, animal, and ecological health. Conventional water treatment processes have limited success in removing MCs without producing harmful byproducts. Therefore, there is an urgent need for cost-effective and environmentally-friendly methods for treating MCs. The objective of this study was to develop sustainable and non-chemical-based methods for controlling MCs, such as using cold plasma and ultra violet (UV) light with titanium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 45 publications
(57 reference statements)
2
7
0
Order By: Relevance
“…While hydrogen peroxide presence in control Microcystis culture medium was lower than that produced by HC + plasma in pure mineral growth medium, hydrogen peroxide concentrations in treated Microcystis cultures were high enough to confirm partial destruction of microcystins and fortification of the inhibitory effect of HC + plasma on Microcystis photosynthesis and growth. Our results also suggest that, during a single cycle, HC + plasma produces an equivalent concentration of hydrogen peroxide to that generally added to surface waters for chemical treatment of cyanobacterial biomass [2,3,7,33]. to confirm partial destruction of microcystins and fortification of the inhibitory effect of HC + plasma on Microcystis photosynthesis and growth.…”
Section: Hydrogen Peroxidesupporting
confidence: 70%
See 3 more Smart Citations
“…While hydrogen peroxide presence in control Microcystis culture medium was lower than that produced by HC + plasma in pure mineral growth medium, hydrogen peroxide concentrations in treated Microcystis cultures were high enough to confirm partial destruction of microcystins and fortification of the inhibitory effect of HC + plasma on Microcystis photosynthesis and growth. Our results also suggest that, during a single cycle, HC + plasma produces an equivalent concentration of hydrogen peroxide to that generally added to surface waters for chemical treatment of cyanobacterial biomass [2,3,7,33]. to confirm partial destruction of microcystins and fortification of the inhibitory effect of HC + plasma on Microcystis photosynthesis and growth.…”
Section: Hydrogen Peroxidesupporting
confidence: 70%
“…to confirm partial destruction of microcystins and fortification of the inhibitory effect of HC + plasma on Microcystis photosynthesis and growth. Our results also suggest that, during a single cycle, HC + plasma produces an equivalent concentration of hydrogen peroxide to that generally added to surface waters for chemical treatment of cyanobacterial biomass [2,3,7,33].…”
Section: Hydrogen Peroxidesupporting
confidence: 57%
See 2 more Smart Citations
“…Another study has found that NTP is a cost-effective, environmentally friendly, sustainable and non-chemical-based promising candidate to destroy microcystins in water which cannot be destroyed by conventional methods. Microcystins are toxins produced by cyanobacteria, and can cause detrimental effects on farm animal health (53). Moreover, DBD-generate -NTP has been shown to inactivate residues of cyanobacteria which cause algal bloom in water (54).…”
Section: Ntp Increases the Microbiological Physical And Chemical Quamentioning
confidence: 99%